Salmon farming in the North – Regulating societal and environmental impacts - Solås, Ann-Magnhild; Kvalvik, Ingrid; Simonsen, Knud; Thorarinsdottir, Ragnheidur Inga; Young, Nathan; Johnsen, Jahn Petter; Sønvinsen, Signe A.; Robertsen, Roy (Nofima, 2020)
Salmon farming is a rapidly growing industry in the North and its sustainable development depends on adequate governance. We have assessed the governance systems for salmon farming in four northern countries, Canada, the Faroe Islands, Iceland, and Norway. In all the countries, the industry is marked by controversies, linked to the environmental and societal impacts of its activities. The question raised is how the authorities address these challenges - what instruments are deployed to achieve a sustainable salmon industry? We have identified both commonalities and differences. The farming of salmon is to a large extent organized in similar ways, with net-pens in the ocean as the dominant production form. In general, the regulations pertaining to the industry have a lot in common. All countries require a license to produce, there are environmental monitoring regimes in place, and the producers are required to report on the same parameters, such as biomass, sea lice counts, disease management, and a range of other statistics. A major difference is the polycentric character of the governance systems in Canada and partly Norway. Still, despite differences in production volume and contextual factors, we see that fairly similar regulatory toolboxes are used to control aquaculture activities. Lakseoppdrett er en næring i vekst i nord. En bærekraftig utvikling av næringen er avhengig av en forvaltning som ivaretar både miljømessig og samfunnsmessige hensyn. Rapporten gir en analyse av fire lands forvaltning av næringen, Canada, Færøyene, Island og Norge. Tross store forskjeller i produksjonsvolum, er utfordringene i stor grad de samme. Forvaltningsverktøyene som benyttes er i hovedsak like, men med noen særegne tilpasninger. Blant annet har landene noe ulik tilnærming til områdeforvaltning og regulering av vekst. Den største forskjellen er likevel den polysentriske innretningen på forvaltningssystemet i Canadas føderale system og kommunenes planmyndighet i Norge.